A case of severe hypothyroidism causing cardiac tamponade associated with lithium intoxication - Yamaguchi, Hiroshi (J Cardiol Cases, 2013)
A 70-year-old man was referred to our emergency department for shortness of breath on exertion and systemic edema. He had been taking lithium carbonate for 2 years (500 mg/day over previous 3 months) for bipolar disorder diagnosed at age 60. He was diagnosed with hypothyroidism accompanied by Hashimoto's disease 2 weeks before hospitalization. Massive pericardial effusion and bilateral pleural effusions were demonstrated by transthoracic echocardiography and computed tomography. Cardiac tamponade occurred on the 3rd day. Pericardiocentesis and thoracentesis were performed once and three times, respectively, because of the acute deterioration of hemodynamic status due to pleural and pericardial effusion. Lithium carbonate is a widely used and effective treatment for bipolar disorder. However, lithium has a narrow therapeutic range and many side effects. An important aspect of this case was the rapid development of severe hypothyroidism, although serum lithium concentration was measured regularly and was maintained within the therapeutic range. It is important to note that lithium can cause serious complications, as in this patient, even if serum lithium concentration is measured regularly and maintained within the therapeutic range. We report the first case of cardiac tamponade caused by hypothyroidism associated with administration of lithium. <Learning objective: Lithium carbonate is a widely used and effective treatment for bipolar disorder. Goiter and hypothyroidism are common clinical side effects of lithium, but the complication of cardiac tamponade has not been reported. An important aspect of this case was the rapid development of severe hypothyroidism, although serum lithium concentration was measured regularly and was maintained within the therapeutic range. Therefore, timely diagnosis and treatment of hypothyroidism by routine assessment of thyroid function should be performed.>